The representation of Vikings in cinema and television - Robeles Delgado, Alberto, author. aut Link Link
1 online resource (264 pages)
Keywords: "Exploring the reception and representation of Viking culture in audiovisual media, particularly in cinema and television, this book provides a comprehensive chronological exploration of films and television programmes produced from the early twentieth century to the present day. Providing a conceptualization of the elements that have shaped the representation of Vikings, both aesthetically and ideologically, and how they have evolved over time. The chapters offer an extensive analysis of this corpus, not only of the audiovisual display about Vikings, but most significantly of the entire context within which these productions were developed. Since cinema reflects its contemporary society, it is crucial to comprehend the motivations behind the representation of Vikings in different cultural, political, and geographical contexts. Regarding the latter, a major distinctive feature of this corpus is its spatial dimension. Films from different film industries such as the United States, Nordic countries, Italy, Russia, or Poland are analysed. Illuminating the variations in the conceptualisations of the idea of Vikings between the different countries, always influenced by their own history and their historiographical association with the Nordic world. Additionally, this book includes an appendix the entire film corpus as a resource for readers to conduct their own research. A History of Vikings in Cinema will be essential reading for students and researchers interested in Vikings in popular culture"-- Provided by publisher.